2017
DOI: 10.1186/s40249-017-0280-8
|View full text |Cite
|
Sign up to set email alerts
|

Building a global schistosomiasis alliance: an opportunity to join forces to fight inequality and rural poverty

Abstract: Schistosomiasis, one of the 17 neglected tropical diseases listed by the World Health Organization, presents a substantial public health and economic burden. Of the 261 million people requiring preventive chemotherapy for schistosomiasis in 2013, 92% of them lived in sub-Saharan Africa and only 12.7% received preventive chemotherapy. Moreover, in 2010, the WHO reported that schistosomiasis mortality could be as high as 280 000 per year in Africa alone.In May 2012 delegates to the sixty-fifth World Health Assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…Essas regiões se situam principalmente próximas as zonas equatoriais e tropicais, com condições climáticas e de habitats (açudes e lagos) que favorecem a proliferação do vetor intermediário (B. glabrata). Outro fato relacionado é a baixa escolaridade formal média dos indivíduos que vivem nessas regiões, o que torna ineficientes políticas de prevenção e higienização contra os vetores e as atitudes de riscos para doença (BROOKER et al, 2006;CABELLO et al, 2016;DISCH et al, 2002;FONSECA et al, 2014;GAZZINELLI et al, 2006;KATZ, 2008;KLOETZEL, 1989;LIMA E COSTA et al 1985;PEREIRA et al, 2010;SAVIOLI et al, 2017;SCHOLTE et al, 2014;SLEIGH et al, 1985;UCHOA et al, 2000). O Semiárido brasileiro é uma área de risco, pois apresenta variáveis favoráveis à disseminação da esquistossomose, seja espacialmente (presença de açudes e lagos), seja em relação ao índice de desenvolvimento humano municipal (< 0,30 em média).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Essas regiões se situam principalmente próximas as zonas equatoriais e tropicais, com condições climáticas e de habitats (açudes e lagos) que favorecem a proliferação do vetor intermediário (B. glabrata). Outro fato relacionado é a baixa escolaridade formal média dos indivíduos que vivem nessas regiões, o que torna ineficientes políticas de prevenção e higienização contra os vetores e as atitudes de riscos para doença (BROOKER et al, 2006;CABELLO et al, 2016;DISCH et al, 2002;FONSECA et al, 2014;GAZZINELLI et al, 2006;KATZ, 2008;KLOETZEL, 1989;LIMA E COSTA et al 1985;PEREIRA et al, 2010;SAVIOLI et al, 2017;SCHOLTE et al, 2014;SLEIGH et al, 1985;UCHOA et al, 2000). O Semiárido brasileiro é uma área de risco, pois apresenta variáveis favoráveis à disseminação da esquistossomose, seja espacialmente (presença de açudes e lagos), seja em relação ao índice de desenvolvimento humano municipal (< 0,30 em média).…”
Section: Introductionunclassified
“…Mundialmente, em torno de 14% dos indivíduos diagnosticados falecem, somente no semiárido brasileiro, esse número chega a 22% (MINISTÉRIO DA SAÚDE, 2018; OMS, 2018), causa mortis associada a desnutrição e desidratação (BROOKER et al 2006;CABELLO et al 2016;GAZZINELLI et al 2016;KLOETZEL et al 1989;SAVIOLI et al 2017;SLEIGH et al 1985). O diagnóstico da esquistossomose é realizado basicamente pela coproscopia quali-quantitativa (Hoffman e Kato-Katz), por hemogramas (eosinofilia, leucopenia, anemia, plaquetopenia, TGO, TGP e fosfatase alcalina), pela ultrasonografia (patognomônico a fibrose e espessamento periportal, hipertrofia do lobo hepático esquerdo e aumento do calibre da mesentérica superior) e por biopsia retal (GRYSEELS, 2004;UTZINGER et al 2015).…”
Section: Introductionunclassified
“…Experiences and lessons from China are important for shaping the schistosomiasis elimination agenda [ 19 ]. However, there is still a need to devise an optimal control strategy with adaptation to local circumstances to facilitate the progress towards the elimination of schistosomiasis in Africa and the Philippines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first conference of the Research Working Group of the Global Schistosomiasis Alliance (GSA) ( http://www.eliminateschisto.org ), held 14–15 June 2016 in Shanghai, People’s Republic of China (PR China), reviewed current progress in schistosomiasis control. Pressing operational research gaps were identified while discussing the new tools and strategies required to make elimination a reality [ 9 ]. For example, it was felt that a highly sensitive diagnostic tool is not only necessary for appropriately targeting populations requiring chemotherapy, but would also facilitate the recognition of the full distribution and extent of damage inflicted by this disease.…”
Section: All Together Nowmentioning
confidence: 99%